Cálculo do entrelaçamento de estados puros com quatro a seis qubits - Oliveira, David Sena (2012)
This thesis is divided in three parts. The first one brings a brief review of the basic concepts about entanglement of quantum states with two and multiple qubits, including the entanglement monotones and the Groverian entanglement measure, which is calculated by a genetic algorithm. The second part is focused on the generation of a entanglement measures that identify only four qubit states with genuine entanglement. Some examples of the calculus of the entanglement of four qubit states, using the proposed measure, when these states are processed by quantum circuits, are presented. In the third part, the proposed measure is extended, to calculate the genuine entanglement of pure six qubits quantum states. Numerical simulations were realized aiming to show the variation, creation and annihilation of the entanglement of pure six qubits states.